Acute Hemiplegia with Chickenpox - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
A case of an 18-month-old girl who developed a right hemiplegia 10 days after onset of varicella infection is reported from the Division of Pediatric Neurology, Istanbul University, Turkey.